Optimizing nitrogen removal with an immobilized biological filler system: realizing stage-independent operational process - Xuyan Liu; Hong Yang; Jiawei Wang (PLoS ONE, 2025)
Due to the operation mode of traditional activated sludge systems, it is difficult for various functional bacteria to exert their respective advantages. In this study, immobilized fillers for hydrolytic acidification, nitrification, and denitrification were developed to allow independent operation at each stage, enhancing nitrogen removal performance of overall process. The results showed that ammonia nitrogen and total nitrogen levels in the effluent stabilized at 0.75–0.83 and 1.5–2 mg/L, respectively, when the total hydraulic retention time (HRT) of the system was 6.4 h and the nitrification unit HRT was 3 h. These values represented significant improvements compared with the traditional activated sludge process. Unit performance tests revealed that reducing the hydrolytic-acidification time to 0 min increased nitrite nitrogen and nitrate nitrogen levels in the effluent of unit A2 to 6.11 ±  0.2 mg/L and 3.67 ±  0.1 mg/L, respectively. This demonstrates that an active hydrolysis - acidification stage is the prerequisite for A2 to fully utilize raw organic matter in the water for remove nitrogen. When raw organic matter in the water bypassed the A2 unit and entered the O1 unit directly, ammonia oxidation rate (AOR) significantly decreased (from 0.32–0.33 to 0.22–0.23 kg/m3 ⋅ d), with further reduction at a low temperature (down to 0.11–0.12 kg/m3 ⋅ d). At this time, the AOR, unaffected by organic matter, decreased only slightly. This indicates that directing organic matter into the nitrification stage is essential for maintaining stability and resisting low temperatures. This process has certain guiding significance for improving nitrogen removal efficiency in municipal wastewater processes.